Sport and National Character in Asia: 亞洲國家的體育特徵 - WATERS, David J.; SMITH, Daniel E. (Asian Journal of Physical Education & Recreation, 2002)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Based on data derived from the International Sport Management Questionnaire (ISMQ) and the National Sport Development Index (NSDI), tendencies are revealed of a nation's development in three domains of sport. These domains (termed Mass Sport, Educational Sport, and Elite Sport) provide insight into national sport culture; low NSDI scores, for instance, divulge a sport delivery system for that domain which is at low level, is de-emphasised, or nonexistent. Data is provided for 14 Asian nations including overall NSDI score as well as the distinct domains mentioned above. From this data, ensuing discussion revolves around a concept of national character of sport for Asian nations such as Japan, China, and Hong Kong, among others. 根據國際體育管理問卷調查(ISA/IQ)和國家體育發展指數(NSDI)的資料顯示，一個國家的體育發展主要表現在三個方面，即群眾體育、學校體育及競技體育。而從這三方面可以了解這一國家的體育文化。例如，NSDI評分低者，體育管理運作系統在這一方面往往處於較低水平，或者不重視，甚至是名存實亡的。這些調查資料涉及14個亞洲國家，包括其上述三個不同方面的狀況極其NSDI評分。根據這些資料，本文圍繞著日本、中國、香港等亞洲國家和地區的體育特征進行了討論。